Food prices and the multiplier effect of export policy - Paolo E. Giordani; Nadia Rocha; Michele Ruta (World Trade Organization (WTO), 2012)
This paper studies the relationship between export policy and food prices. We show that, when individuals are loss averse, food exporters may use trade policy to shield the domestic economy from large price shocks. This creates a complementarity between the price of food in international markets and export policy. Specifically, unilateral actions by exporting countries give rise to a multiplier effect: when a shock in the international food market drives up (down) its price, governments respond by imposing export restrictions (subsidies), thus exacerbating the initial shock and soliciting further export activism. We test this theory with a new dataset that comprises monthly information on trade measures across 125 countries and 29 food products for the period 2008-10, finding evidence of a multiplier effect. Global restrictions in a product (i.e. the share of international trade covered by export restrictions) are positively correlated with the probability of imposing a new export restriction on that product, especially for staple foods. Large exporters are found to be more reactive to restrictive measures, suggesting that the multiplier effect is mostly driven by this group. Finally, we estimate that a 1 per cent surge in global restrictions increased international food prices by 1.1 per cent on average during 2008-10. These findings contribute to inform the broader debate on the proper regulation of export policy within the multilateral trading system.
Keywords: F13; F59; Q02; Q17; 330; Loss aversion; Export policy; Multiplier effect; Food crisis; WTO; Lebensmittelpreis; Nahrungsmittel; Außenhandel; Exportbeschränkung; Multiplikator; Schätzung; Welt